Understanding Resistance vs. Susceptibility in Visceral Leishmaniasis Using Mouse Models of Leishmania infantum Infection - Pérez-Cabezas, Begoña; Cecílio, Pedro; Gaspar, Tiago Bordeira; Gärtner, Fátima; Vasconcellos, Rita; Cordeiro-da-Silva, Anabela (Frontiers in Cellular and Infection Microbiology, 2019)
Every year, up to 90.000 new cases of Visceral Leishmaniasis and 30.000 deaths are estimated to occur worldwide. Such numbers give relevance to the continuous study of this complex form of the disease: both a zoonosis and an anthroponosis; two known etiological agents (Leishmania infantum and L. donovani, respectively); with an estimated average ratio of 1 symptomatic per 10 asymptomatic individuals; and sometimes associated with atypical clinical presentations. This complexity, which results from a long co-evolutionary process involving vector-host, host-pathogen and pathogen-vector interactions, is still not completely understood. The determinants of visceralization are not fully defined and the dichotomy resistance versus susceptibility remains unsolved, translating into obstacles that delay the progress of global disease control. Here, in a way to understand better this dichotomy, we took advantage of different inbred mouse models, with known different susceptibility patterns to Leishmania visceral infection (susceptible BALB/c and C57BL/6 mice and resistant SV/129 mice), and compared dynamically their local and systemic infection-induced immune responses. Overall, our results suggest that C57BL/6 mice develop an intermediate “infection-phenotype” in comparison with BALB/c and SV/129 mouse strains, considering both the splenic parasite burdens and the target organs weights determined. However, the immune mechanisms associated with the control of infection seem to be different in each mouse strain. We observed that both BALB/c and SV/129, but not C57BL/6 mice, show an infection-induced increase of splenic T follicular helper cells. In the other hand, differences detected in terms of CD21 expression by B cells early after infection, together with the quantified anti-Leishmania specific antibodies, suggest that SV/129 are faster than BALB/c and C57BL/6 mice in the assembly of an efficient B-cell response. Additionally, we observed an infection-induced increase in polyfunctional CD4+ T cells in the resistant SV/129 model, opposing and infection-induced increase in CD4+IL-10+ cells in susceptible BALB/c mice. This data align with observations recently reported for L. donovani, the other viscerotropic species, and suggest that not only a mechanism but an interplay of several could be necessary for the control of this parasitic disease.